The attitudes and opinions of pre-service English teachers towards Kurdish-Turkish bilingual education in Turkey - Ayaz, Mehmet Ali (My University, 2014)
This study investigated attitudes and opinions of pre-service English teachers towards Kurdish-Turkish bilingual education in Turkey. The participants of this mixed-methods study were 153 students from the Foreign Language Education Department of a high-ranked state university in the Marmara Region of Turkey. The instrument, ―Bilingual Education Attitudes and Opinions Survey‖ included demographic information followed by 20 items for the quantitative, and 3 open-ended questions for the qualitative part of the study. The instrument was refined based on the feedback of 6 experts following the pilot study. Then it wasreshaped and reformatted before it was used in the study. The quantitative data was transferred to Statistical Program for Social Sciences (SPSS), version 20 for statistical analyses. The reliability of scores (Cronbach‘s α) was .84, a high level of reliability. The qualitative data was transferred to Microsoft Office Word Program, 2013 version for content analysis and thematic analysis. The statistical analyses revealed that a high percentageof the participants (44 %) had high positive attitudes towards Kurdish-Turkish bilingual education in Turkey. The regression analyses showed that men had positively higher attitudes than women whereas ethnicity was not a significant predictor of the attitudes. The content and thematic analysis indicated that some participantswere of the opinion that bilingual education in Turkey could have some advantages in terms ofschool and academic success, human rights, psychological benefits, and cultural diversity. On the other hand, some participants were of the opinion thatbilingual education in Turkey could provoke conflicts, cause separation,affect other minorities negatively and be abused by some people. Some participants also thought that some necessary steps including educating the staff andraising public awareness should be taken to initiate bilingual education, prevailing the peace within the country.

Bu çalışmada, İngilizce öğretmen adaylarının Türkiye‘de Kürtçe-Türkçe çift dilli eğitim yapılmasına ilişkin tutum ve düşüncelerini incelenmiştir. Karma yöntemle hazırlanan bu çalışmaya, Marmara Bölgesi‘ndeki önemli bir devlet üniversitesinin Yabancı Diller Eğitimi bölümünden 153 öğrenci yer almıştır. Çalışma için kullanılan ―Çift dilli Eğitim Tutum ve Düşünce Anketi‖ demografik bilgileri takip eden 20 adet nitel madde ve 3 adet açık uçlu sorudan oluşmuştur. Bu anket, daha önce pilot bir araştırmaya tabi tutulmuş ve 6 uzmanın görüşleriyle düzeltmelere tabi tutulup şekillenmiş ve uygulanmadan önceki son halini almıştır. Nicel veriler, istatistiksel analizler için Sosyal Bilimler için İstatistik Programı (SPSS), sürüm 20‘ye aktarılmıştır. Yapılan güvenirlik analizi sonucunda Cronbach‘ın Alfa‘sı (α) .84, yüksek güvenirlik seviyesi olarak hesaplanmıştır. Nitel veriler ise Microsoft Ofis Word Programı, 2013 sürümüne aktarılmış ve içerik analizi ile tematik analize tabi tutulmuştur. İstatistiksel analizler sonucu, katılımcıların yüksek bir yüzdesinin (% 44) Türkiye‘de Kürtçe-Türkçe çift dilli eğitim yapılmasına ilişkin yüksek tutumlara sahip olduğu ortaya çıkmıştır. Yapılan regresyon analizleri sonucunda, erkek katılımcıların kadınlardan daha yüksek olumlu tutumlara sahip olduğu anlaşılmıştır; ancak, katılımcıların etnik kökenine bakılarak tutumları hakkında yorum yapılamayacağı ortaya çıkmıştır. İçerik analizi ve tematik analiz sonucu bazı katılımcılar, çift dilli eğitimin Türkiye‘ye okul ve akademik başarı, insan hakları, psikolojik faydalar ve kültürel çeşitlilik konularında fayda sağlayabileceğini savunmuşlardır. Öte yandan, bazı katılımcılar da çift dilli eğitimin Türkiye‘de çatışmaya ve bölünmeye yol açabileceğini, diğer azınlıkları olumsuz yönde etkileyebileceğini ve bu durumun bazı insanlar tarafından kötüye kullanılabileceğini savunmuşlardır. Ayrıca bazı katılımcılar Türkiye‘de çift dilli eğitim yapılabilmesi için çalışanların bu doğrultuda eğitilmesi, toplumsal bilincin artırılması ve barışın hakim olması gerektiğini belirtmişlerdir.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2014
Keywords: Bilingual education; Mother tongue; Kurdish-Turkish; Çift dilli eğitim; Anadili; Kürtçe-Türkçe